2021
DOI: 10.1590/1676-0611-bn-2020-1099
|View full text |Cite
|
Sign up to set email alerts
|

Individual niche trajectories in nesting green turtles on Rocas Atoll, Brazil: an isotopic tool to assess diet shifts over time

Abstract: In this study, multi-tissue (yolk and carapace) stable isotope analysis was used to assess individual isotopic niche trajectories of nesting green turtles on Rocas Atoll, off northeastern Brazil, and to reveal a diet shift in the temporal dimension. The diet trajectories of individual green turtles were highly directional, with a stronger component towards decreasing values of δ15N from carapace to yolk. When the green turtles are in their foraging sites (temporal window measured by the yolk samples), they are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The recent CTA extension (Sturbois et al, 2021) showed the importance of plotting trajectory metrics in specifically designed figure concepts, adapted for the representation of dynamics. Building on this, and on previous attempts in SI ecology (Agostinho et al, 2021;Cucherousset et al, 2013;Schmidt et al, 2007), we proposed here two new figure concepts specifically devoted to the representation of dynamics at large spatiotemporal scales: the ITM and the TH (Figures 10 and 11). Here, we have chosen the figure concepts that we deemed the most suitable for each ecological application.…”
Section: Representing Spatio-temporal Dynamics In Stable Isotope Ecologymentioning
confidence: 92%
See 2 more Smart Citations
“…The recent CTA extension (Sturbois et al, 2021) showed the importance of plotting trajectory metrics in specifically designed figure concepts, adapted for the representation of dynamics. Building on this, and on previous attempts in SI ecology (Agostinho et al, 2021;Cucherousset et al, 2013;Schmidt et al, 2007), we proposed here two new figure concepts specifically devoted to the representation of dynamics at large spatiotemporal scales: the ITM and the TH (Figures 10 and 11). Here, we have chosen the figure concepts that we deemed the most suitable for each ecological application.…”
Section: Representing Spatio-temporal Dynamics In Stable Isotope Ecologymentioning
confidence: 92%
“…Temporal dynamics in stable isotope ecology are sometimes represented in 1D or 2D δ space by segment or arrows between consecutive surveys (Agostinho et al, 2021; Guzzo et al, 2011). Here, we propose a trajectory diagram (TD) concept to customize ordination diagrams by adding notably SITA metrics.…”
Section: Trajectory Conceptsmentioning
confidence: 99%
See 1 more Smart Citation